Progress in CO2 Gas Sensing Technologies: Insights into Metal Oxide Nanostructures and Resistance-Based Methods - Yash Ughade; Shubham Mehta; Gautam Patel; Roopa Gowda; Nirav Joshi; Rohan Patel (Micromachines)
The demand for reliable and cost-effective CO2 gas sensors is escalating due to their extensive applications in various sectors such as food packaging, indoor air quality assessment, and real-time monitoring of anthropogenic CO2 emissions to mitigate global warming. Nanostructured materials exhibit exceptional properties, including small grain size, controlled morphology, and heterojunction effects, rendering them promising candidates for chemiresistive CO2 gas sensors. This review article provides an overview of recent advancements in chemiresistive CO2 gas sensors based on nanostructured semiconducting materials. Specifically, it discusses single oxide structures, metal-decorated oxide nanostructures, and heterostructures, elucidating the correlations between these nanostructures and their CO2 sensing properties. Additionally, it addresses the challenges and future prospects of chemiresistive CO2 gas sensors, aiming to provide insights into the ongoing developments in this field.